COVID-19 Infection in Pregnancy: A Descriptive Cross-sectional Study - Mahato, Raj Deb; Yadav, Yogesh Prasad; Pradhan, Tarun (Birat Journal of Health Sciences, 2022)
Introduction: There is diverse evidence regarding the maternal and fetal effect of coronavirus disease 2019 (COVID-19) in pregnancy.Objectives: The objective of this study was to assess the effect of COVID-19 in mother and fetus during pregnancy.Methodology: A descriptive cross-sectional study was conducted during the second wave of COVID-19 in the Department of Obstetrics and Gynaecology at Birat Medical College Teaching Hospital from April 3 to July 3, 2021. All pregnant women admitted in the antenatal ward were sent real-time reverse transcription polymerase chain reaction (RT-PCR) for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. The patients with RT-PCR confirmed SARS-CoV-2 infection were enrolled in the study and followed up until discharged.Results: The COVID-19 positivity rate was 18.0%.The mean age was 24.38 years. Majority of the patients were asymptomatic (79.7%) Among symptomatic patients, 73.3% had fever and respiratory symptoms and 95.9% of women didn't give any history of contact with COVID-19 patients. After confirmed SARS-CoV-2 infection, all pregnant women were immediately shifted to COVID ward, another COVID hospital or advised home isolation. Only one patient had pre-existing hypertension. Among the pregnancy complications, preterm labour was seen in 12.2% followed by premature rupture of membranes in 6.8 %, fetal distress in 5.4%, and still birth in 2.7% of the pregnant women with SARS-CoV-2 infection. The minimum days of hospital stay was one and maximum days of hospital stay were 29 days. Average days of hospital stays was 2.24 days. Only 5.4% of patients who had severe disease required an intensive care unit (ICU) and one patient needed a mechanical ventilator. There was one maternal mortality due to Acute Respiratory Distress Syndrome (ARDS).Conclusion: Symptom, clinical course and severity of COVID-19 in pregnancy is comparable with non-pregnant women with COVID-19 but associated with increases the risk of Preterm labour, Premature rupture of membranes, foetal distress and stillbirth.